Pincaka (Pintar Hanacaraka): Pengembangan Media Berbasis Android Untuk Meningkatkan Kompetensi Menulis Huruf Jawa (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2022)
The students of grade 11th MAN 2 Semarang have difficulty in writing Javanese script-based text. Hence, Android-based Pincaka (pintar hanacaraka) media is necessary to help them practice writing Javanese scripts. This research aims to develop Android-based Pincaka learning media. This research belongs to Research and Development which was done in five steps, including potentials and problems analysis, gathering information, product design, design validation, and design revision. The data was collected through observation, interview, and questionnaire. Then, the data were analyzed by using the descriptive qualitative analytical technique. The result of the study shows that students and teachers need supported media to learn to write Javanese scripts text. The content of the media consists of materials, exercises for writing various Javanese scripts text, and evaluation. The results of the media validation test obtained an average score of 3,875, while the material validation showed an average score of 3 from a range of 1 to 4. Therefore, the android-based pincaka (pintar hanacaraka) media can be used and developed to support the material lesson of writing Javanese text, both in class XI MAN 2 Kota Semarang and class XI SMA/SMK/MA in general.